Burnout and Softskill on Vocational Students’ Performance - Syamna, Danial Khaled; Rusli, Lathiefa; Firmansah, Yayan (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim: The phenomena of burnout and soft skill development are no longer just an individual issue, but has become a serious challenge to the student’s performance This study aims to examine the influence of burnout and soft skill on vocational students’ performance. Design/Methode/Approach: The research used quantitative descriptive methods. Data was collected by distributing questionnaires to 172 sample of 3rd year student at a vocational school in Ponorogo. Research Finding: The findings gleaned from the study reveal a noteworthy correlation, indicating that not only do burnout and soft skills play integral roles in shaping the academic landscape, but they also exert a positive influence on students’ overall performance. This suggests that managing burnout and cultivating essential soft skills contribute synergistically to an enhanced educational experience, fostering an environment conducive to academic success. Theoretical contribution/Originality: The novelty of this study lies in its dual focus on the interplay between burnout, soft skills, and academic performance within the context of vocational education. By focusing on such a context, this research contributes a unique perspective to the existing body of literature. Practitioner/Policy implication: This research holds significant implications for vocational schools. Vocational schools can leverage this research to strategically prioritize the enhancement of specific soft skills that directly support students’ performance. Research limitation: The main limitation of this study was the data was only carried out at certain times and classes, so it was not comprehensive for all students who were facing some free activities. Therefore, the burnout and lack of soft kill can only be hypothesized but cannot be objectively proven. Thorough research is needed on all students to be able to answer the questions objectively.